WORKPLACE MENTAL HEALTH AND JOB PERFORMANCE OF OIL SERVICING FIRMS IN PORT HARCOURT (American Journal of Research in Humanities and Social Sciences, 2023)
The objective of this paper is to investigate workplace mental health and job performance of oil servicing firms in Port Harcourt. The study adopted a cross sectional research approach, which is a form of the quasi experimental research design in testing the relationship between the variables under study. Spearman Rank Correlation Coefficient and partial correlation were used in testing the hypotheses. The study shows a positive relationship between job performance and staff mental health in oil servicing firms. The relationship between employee mental health and job performance has been one of the key concerns in workplace. However, extant studies suffer from incomplete results due to their focus on developed economies’ contexts and the unclear path of employee mental health’s impact on performance. In this paper, we investigate the mechanism of employee mental health influencing job performance. We use the data of oil servicing firms in Port Harcourt to test these hypotheses. Drawing on a sample of 10 firms from Port Harcourt, we find that employee mental health positively impacts job performance, and such relationship is mediated by innovative behavior and work engagement. The findings not only enrich the discipline’s knowledge on mental health in an emerging economy setting but also extend the implications of mental health, innovative behavior, and work engagement to job performance.